2011
DOI: 10.1182/blood-2011-07-343566
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte ligands for endothelial selectins: specialized glycoconjugates that mediate rolling and signaling under flow

Abstract: Reversible interactions of glycoconjugates on leukocytes with P-and E-selectin on endothelial cells mediate tethering and rolling of leukocytes in inflamed vascular beds, the first step in their recruitment to sites of injury. Although selectin ligands on hematopoietic precursors have been identified, here we review evidence that PSGL-1, CD44, and ESL-1 on mature leukocytes are physiologic glycoprotein ligands for endothelial selectins. Each ligand has specialized adhesive functions during tethering and rollin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
393
0
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 412 publications
(416 citation statements)
references
References 115 publications
4
393
0
10
Order By: Relevance
“…L-selectin is expressed on the surface of most circulating leukocytes, facilitating leukocyte migration into secondary lymphoid organs and inflammation sites. P-and E-selectin, expressed on inflamed endothelium 22 , are likewise responsible for the accumulation of blood leukocytes at sites of inflammation by mediating the adhesion of cells to the vascular lining 23 . Analysis of the gene expression profiles revealed that the mRNA expression of SELL was upregulated in acne lesions 24 .…”
Section: Discussionmentioning
confidence: 99%
“…L-selectin is expressed on the surface of most circulating leukocytes, facilitating leukocyte migration into secondary lymphoid organs and inflammation sites. P-and E-selectin, expressed on inflamed endothelium 22 , are likewise responsible for the accumulation of blood leukocytes at sites of inflammation by mediating the adhesion of cells to the vascular lining 23 . Analysis of the gene expression profiles revealed that the mRNA expression of SELL was upregulated in acne lesions 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although much of our knowledge of glycoTs regulating selectin-ligand synthesis is derived from mice, these animals differ from humans particularly with respect to E-selectin and its ligands (1,6). In this regard, although E-selectin binding to mouse granulocytes is completely lost upon pronase digestion, it is only partially reduced in human cells (7,8).…”
mentioning
confidence: 95%
“…Together, the rolling experiments with L-E cells and stimulated HUVEC confirm a more significant role for FUT9 and FUT7, as opposed to FUT4, during HL-60 rolling on E-selectin. The apparent importance of FUT9 in human leukocyte adhesion is not entirely unexpected because it is well recognized that the E-selectin ligands in human leukocytes differ from those in the mouse (1,5). In particular, E-selectin ligands on mouse but not human neutrophils are pronase-sensitive (7,8).…”
Section: Fut7mentioning
confidence: 99%
See 1 more Smart Citation
“…Transfection of fucosyltransferase VII into different cell lines conferred the ability to bind to E-selectin in flow chamber experiments (39,40), indicating that the glycoprotein requirements for E-selectin binding may be more relaxed than for Pselectin. The three glycoproteins PSGL-1, CD44, and ESL-1 on murine leukocytes are the most physiologically relevant E-selectin ligands (41). Elimination of PSGL-1 impairs E-selectin-mediated tethering in vitro and in vivo (42).…”
Section: Discussionmentioning
confidence: 99%